Gambaran Sedentary Lifestyle Siswa SLTA Sederajat di Kabupaten Madiun Tahun 2022 - Muhammad Nur Qosim; Kurnia Dwi Artanti (Universitas Airlangga, 2023)
Background: COVID-19 pandemic has had an impact on various sectors of life, one of which is on physical and mental health. Limiting the social impact of lifestyle changes with less physical activity and longer sitting duration. Moreover, today's modern teenagers along with technological advances become a population that has less physical activity. Objectives: This study aims to determine the description of sedentary lifestyle during the COVID-19 pandemic in high school students equivalent in Madiun Regency. Methods: This research method uses a quantitative design with a descriptive analysis research design. The research sample was 247 students from 4 schools in Madiun Regency. Data was collected by distributing the ASAQ (Adolescent Sedentary Activity Questionnaire) questionnaire to measure a sedentary lifestyle. The analysis used in this research was descriptive analysis using SPSS. Results: This study shows that during the COVID-19 pandemic, equivalent high school students in Madiun Regency had a sedentary lifestyle in the high category of 52.2%, 45.7% in the medium category, and 2.0% in the low category. Conclusions: During the COVID-19 pandemic, high school students in Madiun Regency experienced an increase in their sedentary lifestyle in terms of time duration and had a high sedentary lifestyle. The school should provide education to students regarding healthy lifestyles by exercising regularly, reducing lifestyle activities, making sports week programs such as healthy friday.